Computational modelling of electrostatic interactions between colloidal patchy particles - Stankiewicz, Malgorzata (2021)
Controlled self-organisation of patchy colloidal particles depends mainly on weak forces - reversible electrostatic interactions. Developments in the modelling of patchy particles can help understanding more in-depth the influence of self-assembly systems and predict desired structure formation. The report presents the implementation of non-uniform charge distribution with the ability to modelling desired size patches. A range of trends is displayed to demonstrate the reliability and robustness of the model. Following this, a recreation of results, analysis and prediction for experimental work published in 2020 by Mehr et al. is presented. As an additional extension of this project, atomic-scale small systems were explored by applying charged dielectric polarisable particles model. The accuracy of the classical model was investigated, and the ability to approximate neutral atoms and ions was examined.